Binding of Citreoviridin to Human Serum Albumin: Multispectroscopic and Molecular Docking. (21st April 2015) - Hou, Haifeng; Qu, Xiaolan; Li, Yuqin; Kong, Yueyue; Jia, Baoxiu; Yao, Xiaojun; Jiang, Baofa
Abstract : Citreoviridin (CIT), a mycotoxin produced by Penicillium citreonigrum, is a common contaminant of wide range of agriproducts and detrimental to human and animal health. In this study, the interaction of CIT with human serum albumin (HSA) is researched by steady-state fluorescence, ultraviolet-visible (UV-Vis) absorption, circular dichroism (CD) methods, and molecular modeling. The association constants, binding site numbers, and corresponding thermodynamic parameters are used to investigate the quenching mechanism. The alternations of HSA secondary structure in the presence of CIT are demonstrated with UV-Vis, synchronous fluorescence, and CD spectra. The molecular modeling results reveal that CIT can bind with hydrophobic pocket of HSA with hydrophobic and hydrogen bond force. Moreover, an apparent distance of 3.25 nm between Trp214 and CIT is obtained via fluorescence resonance energy transfer method.